The Essence of Discrete Mathematics - Neville Dean (Pearson Education Limited/ Dorling Kindersley India Pvt.Ltd., 2011)
This book is appropriate for a first course in Discrete Mathematics. The fundamentals of sets and logic supply the foundations for learning and provide clear instructions on how to calculate values for mathematical expressions for small finite sets.